2015
DOI: 10.1055/s-0034-1398559
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Mitochondrial SDHB Expression: What is its Role in Diffuse Thyroid Lipomatosis?

Abstract: Diffuse lipomatosis of the thyroid gland is a very rare disease, characterized by extensive infiltration of thyroid parenchyma by mature adipose tissue, usually not accompanied by amyloid fibrils deposition. The pathophysiology of adipose tissue infiltration in the thyroid gland remains unknown. We report a clinical case of a diffuse thyroid lipomatosis, whose immunohistochemical study of succinate dehydrogenase - subunit B (SDHB) revealed loss of expression of this protein in the follicular or adipose cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…Lau et al . (6) have recently published a possible relationship between the mutation of the mitochondrial protein succinate dehydrogenase-subunit B and the abnormal differentiation of adipose tissue in thyroid lipomatosis.…”
Section: Discussionmentioning
confidence: 99%
“…Lau et al . (6) have recently published a possible relationship between the mutation of the mitochondrial protein succinate dehydrogenase-subunit B and the abnormal differentiation of adipose tissue in thyroid lipomatosis.…”
Section: Discussionmentioning
confidence: 99%
“…Liposarcoma of the thyroid is a rare type of malignancy that is classified according to its histopathological criteria into well-differentiated, myxoid, round cell, pleomorphic, and dedifferentiated types. At presentation, the majority of liposarcomas are found to be extended beyond the capsule [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Schroder et al suggested that adipose tissue may be caused by meta-plasia of stromal fibroblasts due to tissue hypoxia or senile involution [ 17 ]. More recently, Lau et al suggested a possible relationship between diffuse lipomatosis and loss of expression of a protein called succinate dehydrogenase-subunit B in the follicular or adipose cells [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…SHDB and VEGFA are upregulated genes in the RR variety associated with the beta-oxidation of fatty acids and with angiogenesis, migration, and cellular growth [37], respectively. Different studies using knockout mice for the SHDB gene reported that the lack of its expression activates the energy metabolism, producing obesity resistance and the development of thyroid lipomatosis [38]. VEGFA gene has been widely studied due to its influence in many cellular processes, such as nutrient diffusion and angiogenesis.…”
Section: Gene Ontology and Pathways Enrichment Analysismentioning
confidence: 99%